Clash of the Giants - Williams, D. H. (Defending and Defining the Faith: An Introduction to Early Christian Apologetic Literature, 2020)
This chapter considers the work of Origen, whose one and only anti-pagan work elevated Christian standing in a culture that prized philosophical argumentation and intellectual attainment as among the higher goods. It was the first draft, as it were, “of a sustained Christian reflection of the evangelization of Hellenistic culture,” and the first one to survive. Origen had produced multivolume projects on a larger scale than Contra Celsum (Against Celsus), but it is this work that has come down to us, complete, in eight volumes. A great deal is known about both Origen and his literary efforts, including his work against the Christian critic Celsus. Although Celsus had been dead for seventy years or so, it is supposed that his arguments had been effectual enough to cause such severe Christian trepidation that Origen was asked by his patron, Ambrosius, to construct a refutation.
paid